SETD5 gene mutation as the cause of short stature - Roztoczyńska, Aleksandra Maria; Roztoczyńska, Dorota; Pyrkosz, Antoni; Mazur, Artur (Pediatria Polska - Polish Journal of Paediatrics, 2024)
An 8-year-old boy was referred to the Clinic of Pediatric Endocrinology due to his short stature. The child comes from P II B II, was born naturally, with birth weight 2970 g. He had dysmorphism and a height of 118 cm (3rd centile). Growth hormone (GH) deficiency and other causes of short stature were excluded. A genetic panel was performed using next generation sequencing, which revealed a pathogenic variant in the SETD5 gene, with which growth deficiency is not typically associated. Literature reports suggest that genetically determined conditions with transcriptional effects, GH deficiency, and intellectual disability may overlap phenotypically. The most likely cause of short stature in this case is a genetic mutation in the SETD5 gene. The boy requires multidisciplinary care, including auxological assessment, growth monitoring, puberty assessment, and pediatric and endocrinological care. All children with short stature and dysmorphic features or body proportion abnormalities who receive GH therapy require genetic testing.